Pengembangan Video Animasi Pembelajaran Fisika Berbasis Adobe Premiere Pro Pada Materi Gelombang Bunyi - Syah Tabroni; Indica Yona Okyranida; Dandan Luhur Saraswati (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The purpose of this research is to know the process of development and feasibility of the animation video learning based on adobe premiere pro on concept of the sound wave. This research is research and development, the models of construction adopted by ADDIE (Analysis, Design, Develop, Implementation and Evaluation). The product is tested for eligibility through validation testing by the content experts, media experts, and language experts. Based on the analysis of the data acquired that a animation video learning based on adobe premiere pro is declared feasible by the media experts with an average percentage of 86,18%, content experts with a precentage of 85,77% and te language experts with a precentage of 90,00%. Which belongs to the category of “excelent”. From the study, it can to be concluded that learning deserves media of adobe premiere pro use in the learning process on the school.